Locating Chicago's charter schools: A socio-spatial analysis - Jennifer C. LaFleur (Arizona State University, 2016)
This project contributes to the body of research examining the implications of the geographic location of charter schools for student access, especially in high-poverty communities. Using geographic information systems (GIS) software, this paper uses data from the U.S. Census American Community Survey to identify the socioeconomic characteristics of the census tracts in which Chicago's charter schools tend to locate. Echoing the findings of other researchers who have examined charter school locational patterns, the present analyses found evidence of a "ceiling effect" by which many charter schools appear to locate in Chicago's higher-needs census tracts, broadly cast, but avoid locating directly within those that are highest-need. The findings suggest that because Chicago's charter schools face per-pupil expenditures that are often up to 20% less than those of traditional public schools, they may strategically leverage location to help shape student enrollment. By frequently locating near, but not directly within highest-need communities, charter schools may find it easier to attract a quorum of relatively higher achieving students who are less expensive to educate, therefore increasing their chances of meeting academic benchmarks and retaining their charters. By extending the findings of other researchers to the context of Chicago-where charters represent an ever-increasing share of the public school market-the present analyses may inform future revisions to the policies governing the authorization of charter schools in Chicago, with the goal of increasing access for highest-need students.